(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
Analysis of the communicative functions of the politeness category in three works. Politeness is a form of social interaction specific to culture, which plays an important role in ensuring the new communication of the participants in the speech. The work studies how politeness strategies are expressed through various speech styles, such as attention, sincerity, respect, and the effect of fixation. From the point of view of communicative functions, the role of the politeness category in communication, social norms, conflict resolution, and image maintenance, is examined. The strategy of politeness in various contexts in the meeting serves to improve the communicative means.